Band anti-crossing modelling on tailored Ga1-xInxNyAs1-y band gap energy based nitrogen fraction - Abd Samad, Muhammad Izzuddin; Mohamad, Khairul Anuar; Nordin, Mohammad Syahmi; Nayan, Nafarizal; Alias, Afishah; Othman, Marinah; Boland-Thoms, Adrian; Vickers, Anthony John (2019)
This paper deals with a Band Anti-Crossing (BAC) modelling to investigate the tailoring of band gap energy of Ga1-xInxNyAs1-y alloy based on nitrogen fractions. Three different numerical methods have been adopted to estimate the extended state of conduction band (